Association between serum retinol and overall and cause-specific mortality in a 30-year prospective cohort study - Jiaqi Huang (Nature Portfolio, 2021)
Vitamin A, of which retinol is the major form in the circulation, is a determinant of human health but whether vitamin A status is associated with mortality is not well understood. Here the authors report that in a prospective observational analysis of 29 104 men, higher serum retinol associates with lower risk of overall and cause-specific mortality.